From Murky Salty Water to Crystal-Clear Fresh River Flow: Pre-service Teachers‟ Assessment Perceptions (Journal of Education and Development, 2022)
This qualitative study followed the development of 94 pre-service teachers‟ assessment perceptions in an introductory course on student assessment. Analysis of the students‟ retrospective and end of course perceptions identified five assessment dimensions. Considerable shifts were detected in each dimension: from summative to formative assessment, from negative to positive assessment perceptions, from perceiving assessment as a simple concept to a complex and multifaceted one, from hierarchical to dialogical perceptions of teacher-student relationships. The findings indicate the potential impact of training in assessment literacy on future teachers‟ conceptual framework regarding assessment for learning and hold implications for teacher education programs.